2002
DOI: 10.1016/s0009-2614(02)00986-7
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR patterns of C36H2x fullerene hydrides

Abstract: Calculations of 13 C nuclear shieldings for low-energy isomers of C 36 H 2x ðx ¼ 2; 3Þ suggest that it should be possible to use experimental 13 C shifts, when these become available, to distinguish the isomeric form of the underlying fullerene cage and, in the case of isomers based on the six-fold symmetrical cylindrical fullerene cage 36:15, the degree of polar hydrogenation. Ó

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Ref. 38 reported a detailed analysis of the trends in the carbon‐13 NMR spectra of various‐size fullerenes that were produced experimentally. In a similar vein, calculations can help to understand properties that depend on the finite size of the GQDs as well as their boundary structure.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. 38 reported a detailed analysis of the trends in the carbon‐13 NMR spectra of various‐size fullerenes that were produced experimentally. In a similar vein, calculations can help to understand properties that depend on the finite size of the GQDs as well as their boundary structure.…”
Section: Introductionmentioning
confidence: 99%
“…The first theoretical study on C 36 has been reported by Grossman and co-workers, which revealed that the energetically most favorable structures of C 36 fullerene are associated with D 6 h and D 2 d symmetry using density functional calculation with local density approximation (LDA) and generalized gradient approximation (GGA) methods. Subsequently, a considerable amount of theoretical work has been published in the literature dealing with the C 36 fullerene system. Depending on the method of calculation, the ground-state structure of C 36 cage is found to be either D 2 d or D 6 h ; however, in most of the reports it is clearly stated that the D 2 d singlet state, D 6 h singlet state, and D 6 h triplet state are almost isoenergetic. ,,,, Apart from U@C 36 , which is detected in FT-ICR mass spectrum, there is no experimental evidence available for any other endohedral C 36 derivative. Even for the U@C 36 system, no further theoretical or experimental information is available on its structure and characterization.…”
Section: Introductionmentioning
confidence: 99%
“…CS tensors which are reproduced reliably by performing high-level quantum chemical calculations provide highly valuable information about electrostatic environment around the nucleus, which feels subtle changes by any perturbations [30]. The calculations of NMR parameters using ab initio techniques have found the ability of quickly evaluating and correlating the magnitude of CS tensors with variations in bond angles, bond lengths, and the nearest neighboring interactions, which has increased the significance of utilizing these parameters in exploring molecular structures [31,32].…”
Section: Introductionmentioning
confidence: 99%